Heart disease in chronic kidney disease - review of the mechanisms and the role of dialysis access - Malik, Jan (The journal of vascular access, 2018)
Cardiovascular complications are responsible not only for the high mortality, but also the morbidity of end-stage renal disease patients. Cyclic changes of fluid load, together with the altered metabolism, are responsible and are mirrored in many particular parts of the heart. A review of the mechanisms involved is presented and the role of dialysis access is highlighted.
Keywords: kardiorenální syndrom; výsledek terapie; Chronic kidney disease; Ventricular Function, Left; Catheterization, Central Venous; funkce levé komory srdeční; Risk Factors; Kidney Failure, Chronic; Heart failure; chronické selhání ledvin; Heart Diseases; dialýza ledvin; katetrizace centrálních vén; Water-Electrolyte Balance; Cardio-Renal Syndrome; Echocardiography; Arteriovenous Shunt, Surgical; Hemodynamics; arteriovenózní zkrat; Treatment Outcome; Hemodialysis; Renal Dialysis; Peripheral Vascular Diseases; lidé; Vascular access; Humans; rizikové faktory; přesuny tekutin; nemoci srdce; onemocnění periferních cév; hemodynamika; Fluid Shifts; vodní a elektrolytová rovnováha